Gender Differences in Clinical and Epidemiological Profile of Adult Patients with Vitiligo - Poudyal, Yogesh; Jha, Chandra Bhal; Parajuli, Niraj (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Vitiligo is an acquired disorder of skin characterized by white macules. Though there are many studies describing clinical and epidemiological features of vitiligo; there are few studies which have attempted to see the differences between male and female. Understanding the gender differences in clinico-epidemiological features will help to find the direction for further research in understanding pathogenesis. The objective was to find the gender wise differences in clinico-epidemiological pattern of vitiligo. MATERIAL AND METHODS This was cross sectional study done at Dermatology and Venereology out-patient clinic of Universal College of Medical Sciences Teaching hospital, Bhairhawa, Nepal from January 1, 2015 to December 31, 2016. Consecutive sampling technique was used and the cases of 18 years and above were taken. Chi-square test, multi-variate logistic regression, two sample t-tests were used to analyze the data. RESULTS The total number of case was 190. Female to male ratio was 1.38:1. Vitiligo vulgaris was seen more in female and mucosal vitiligo more in male and the difference was statistically significant. However, there was no statistically significant difference among gender in family history, duration of disease, mucosal and hair involvement, history of recurrence and various age groups. CONCLUSION Vitiligo vulgaris is seen more in female and mucosal vitiligo is seen more in male. This study has strengthened the evidence regarding the difference noted in clinic-epidemiological aspect of vitiligo. There should be more studies, so that more patterns in gender differences could be understood, and this will help in understanding the pathogenesis of vitiligo.